Position and Legal Certainty in the Decision of the Honorary Board of Election Organizers (After the Constitutional Court Decision Number 32/PUU-XIX/2021) - Dedi Supriyadi; Ende Hasbi Nassaruddin; Beni Ahmad Saebani (West Science Social and Humanities Studies, 2023)
The purpose of this study is to find out the legal regulations regarding legal certainty in the decision of the honorary board of election organizers based on the decision of the Constitutional Court Decision Number 32/PUU-XIX/2021). The method used in this study is the Normative Juridical approach. Juridical-normative research was chosen because it affirms the existence of ethical norms and legal norms as part of the norm system that applies in society. The results of the study concluded that the Urgency of DKPP is a vital and significant institution to deal with violations of the Election Organizer's code of ethics and is a unified function of the Election Organizer; The nature of the legal certainty of the decision of the Election Organizing Honor Board (DKPP) after the Constitutional Court decision Number 32/PUU-XIX/2021 is not recognized and confirms that the DKPP is not a judicial institution, so the DKPP decision is a decision of a State Administration official who can be the object of a lawsuit at the State Administrative Court; and it is necessary to establish an ethical court through law, not only limited to DKPP. where enforcement is carried out through an independent, impartial, and open judicial process, namely the Court of Law for legal matters, and the Court of Ethics for ethical issues.